2020
DOI: 10.1093/abbs/gmaa167
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LVRN impedes the invasion of trophoblasts by inhibiting epithelial–mesenchymal transition

Abstract: Laeverin (LVRN) was first detected on the outer layer of the chorion laeve and migrating extravillous trophoblasts (EVTs). It is an enzyme that plays an important role in the placentation and pathophysiology of preeclampsia (PE). Previous studies have indicated that LVRN may be required for the invasion of human trophoblast cells. Paradoxically, LVRN was found to be highly expressed in the trophoblasts of PE patients with impaired invasive capacities. In this study, we detected the expression of LVRN in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Our previous study has indicated that PLAC8 may promote autophagic activity and improves the growth priority of human trophoblast cells [41]. We have also demonstrated that the overexpression of AQPEP//LVRN could influence the invasion of trophoblast [42]. In addition, NONHSAT003875/ miR-363/EGR1 regulatory network in the carcinoma -associated fibroblasts was confirmed to control the angiogenesis of PSTT [43].…”
Section: Discussionmentioning
confidence: 67%
“…Our previous study has indicated that PLAC8 may promote autophagic activity and improves the growth priority of human trophoblast cells [41]. We have also demonstrated that the overexpression of AQPEP//LVRN could influence the invasion of trophoblast [42]. In addition, NONHSAT003875/ miR-363/EGR1 regulatory network in the carcinoma -associated fibroblasts was confirmed to control the angiogenesis of PSTT [43].…”
Section: Discussionmentioning
confidence: 67%